2013
DOI: 10.1016/j.jcdr.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of voltage criteria for left ventricular hypertrophy in adult hypertensives in south-western Nigeria

Abstract: Out of the 4 ECG criteria, Araoye code system, Cornell and Sokolow-Lyon criteria compared favorably well with echocardiography and may be used in the initial assessment of LVH in adult hypertensive subjects. However, a combination of any of the 3 criteria with Gubner-Ungerleider criterion will be more clinically useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(21 reference statements)
3
8
1
Order By: Relevance
“…Furthermore, the V3 lead is closer to the LV and is probably less influenced by variations in the distance between the myocardium and the leads. However, our finding is consistent with the report of a few studies [4] [32] [37] of a better performance of Sokolow-Lyon index vs. Cornell indexes. The exact mechanism underlying the better performance of Sokolow-Lyon index is not clear and could be related to age and BMI of the studied patients as well as the modality of LVM indexation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, the V3 lead is closer to the LV and is probably less influenced by variations in the distance between the myocardium and the leads. However, our finding is consistent with the report of a few studies [4] [32] [37] of a better performance of Sokolow-Lyon index vs. Cornell indexes. The exact mechanism underlying the better performance of Sokolow-Lyon index is not clear and could be related to age and BMI of the studied patients as well as the modality of LVM indexation.…”
Section: Discussionsupporting
confidence: 93%
“…Among identified factors, left ventricular hypertrophy (LVH) is thought to play a central role in the development and progression of CVD [3]. LVH has been reported to be associated with cardiac arrhythmias, ischemic heart disease, congestive heart failure, and sudden death [4]. Given the prognostic importance of LVH, accurate diagnosis and appropriate management of LVH have become a major component of the care of patients with hypertension [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research focuses on healthy individuals and brings findings about differentiation between normal and pathological means in young healthy sedentary males. It contributes to previous scientific findings and shows that voltage criteria do little to reflect left ventricular mass [1,21]. On the other hand, we found that false positive meanings of Sokolow-Lyon Product prevail in 30 % of healthy male subjects, however, its ability to reflect LVM is the highest and statistically significant among all criteria under investigation in subjects with normal BMI (< 25).…”
Section: Discussionsupporting
confidence: 74%